The Effect of Purified Wastewater on the PhysicoChemical Properties of Agricultural Soils in Chaouia in Morocco - Dyaa Abou-tammame (Polish Society of Ecological Engineering (PTIE), 2022)
The aim of this study was to assess the impact of the reuse of purified wastewater from the wastewater treatment plant in the city of Settat on the physicochemical quality of agricultural soils compared to the agricultural soils irrigated by rainwater in the region of Chaouia in Morocco. The results obtained showed that despite the great fertilizing value of the purified wastewater, a slight increase in salinity was noted; they also reveal a significant difference in pH. The accumulation of sodium, total limestone and active limestone in the soil increased significantly in the soils irrigated by treated wastewater; in contrast, calcium increased significantly in the soils irrigated by rainwater.No significant differences were recorded for humidity, electrical conductivity, ammonium, nitrates, phosphorus, potassium, organic matter, total nitrogen or cation exchange capacity.